Fifteen years of military research in five military schools and in the National Defense College of the Philippines, 1966-1980 an analysis with an annotated bibliography - Parajas, Mary Lou R. (1983)
The purpose of this study is to bibliographically control military researches conducted in five AFP schools and the National Defense College of the Philippines, classify the available military researches according to the AFP Subjective Classification System and establish where they are located. This compilation of researches from 1966 to 1980 further gives an insight on the frequencies of studies conducted in various AFP subject areas.